2022
DOI: 10.3389/fped.2022.913583
|View full text |Cite
|
Sign up to set email alerts
|

Time to death and its predictors among neonates who were admitted to the neonatal intensive care unit at tertiary hospital, Addis Ababa, Ethiopia: Retrospective follow up study

Abstract: BackgroundsNeonatal death is the major problem in developing world. Burden and predictors of neonatal mortality vary across countries and even among regions of a country, so understanding the problem concerning these factors is essential to overcome the problem. Therefore, this study aimed to determine time to death and its predictors of neonatal mortality among neonates who were admitted to the neonatal intensive care unit of Tertiary Hospital, Addis Ababa, Ethiopia.MethodsA hospital-based retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
5
6
0
Order By: Relevance
“…These results align with a study conducted in the NICU of a tertiary hospital in Addis Ababa (22), where approximately 70% of neonatal deaths were registered during the early neonatal period. Similarly, an investigation conducted in a referral hospital in Cameroon reported that over 74.2% of deaths occurred during the early neonatal period (9).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These results align with a study conducted in the NICU of a tertiary hospital in Addis Ababa (22), where approximately 70% of neonatal deaths were registered during the early neonatal period. Similarly, an investigation conducted in a referral hospital in Cameroon reported that over 74.2% of deaths occurred during the early neonatal period (9).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, a study conducted in in Addis Ababa (31), which consistently reported a higher likelihood of mortality among neonates with sepsis compared to those without. The presence asphyxia, and respiratory distress syndrome (RDS) were significantly associated with neonatal mortality (43).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations